2019
DOI: 10.1002/fuce.201900065
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Studies of Novel Cobalt Free (Nd0.9La0.1)1.6Sr0.4 Ni0.75Cu0.25O3.8 (NLSNC4) Cathode Material for IT‐SOFCs

Abstract: A novel cathode material of (Nd0.9La0.1)1.6Sr0.4Ni0.75Cu0.25O3.8 (NLSNC4), is synthesized by solid state reaction and is further investigated in combination with samarium doped ceria (SDC) as composite cathodes including 0, 10, 30, 50, and 70 of SDC electrolyte phase. The X‐ray diffraction analysis showed that NLSNC4 was produced in pure phase and was chemically compatible with SDC electrolyte. Electrical conductivities of single phase and composite cathode materials along with their electrochemical performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Therefore, La 1−x Sr x CoO 3 (LSC)-and La x Sr 1-x Co y Fe 1-y O 3-d (LSCF)based systems are the most promising [11,18]. There are however alternative perovskite-type cathode materials, such as Sm 0.7 Sr 0.3 Co 3 [19], BaCo 0.7 Fe 0.2 Nb 0.1 O 3 [20], cobalt free (Nd 0.9 La 0.1 ) 1.6 Sr 0.4 Ni 0.75 Cu 0.25 O 3.8 [21], La 0.8 Sr 1.2 Fe 0.9 Cu 0.1 O 4 [22], and BaFe 1−x Cu x O 3 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, La 1−x Sr x CoO 3 (LSC)-and La x Sr 1-x Co y Fe 1-y O 3-d (LSCF)based systems are the most promising [11,18]. There are however alternative perovskite-type cathode materials, such as Sm 0.7 Sr 0.3 Co 3 [19], BaCo 0.7 Fe 0.2 Nb 0.1 O 3 [20], cobalt free (Nd 0.9 La 0.1 ) 1.6 Sr 0.4 Ni 0.75 Cu 0.25 O 3.8 [21], La 0.8 Sr 1.2 Fe 0.9 Cu 0.1 O 4 [22], and BaFe 1−x Cu x O 3 [23].…”
Section: Introductionmentioning
confidence: 99%
“…One solution focuses on utilizing highly active component materials, starting with electrode materials of higher catalytic activity or electrolytes of higher ionic conductivity. However, the selection of SOFC component materials that reduce temperature while remaining cost-effective is quite limited [169,170]. Alternatively, temperature reduction can be achieved through improvements in manufacturing processes, such as nanostructured components and thin-film electrolytes [171,172].…”
Section: Options To Decrease the Operating Temperature Of Sofcmentioning
confidence: 99%
“…Experimental evidence has shown that A-site deficiency can improve both electronic and ionic conductivity of Ln x Sr 1– x TiO 3−δ compounds. , As a result of creating A-site deficiency, the concentration of oxide ion vacancies and reducibility of Ti 4+ to Ti 3+ (leads to higher electronic conductivity) increases compared to nondeficient lattice. , Furthermore, A-site deficiency has also been used for mitigating Sr segregation, which may be a significant factor contributing to the deactivation of perovskite oxide surfaces and the subsequent degradation of SOC electrode performance. , …”
Section: Introductionmentioning
confidence: 99%